Novel biocatalytic routes for the synthesis of small cyclic molecules - Hegarty, Eimear (2020)
The catalytical asymmetric reduction of small cyclic prochiral ketones with the formation of optically pure alcohols and amines is a fundamentally important reaction in synthetic organic chemistry. However, achieving selectivity using traditional synthetic methodology is challenging, particularly when the prochiral ketone has minimal discrimination between the two side chains. In light of this, new biocatalytic strategies for the enantioselective preparation of small cyclic molecules starting from readily available and inexpensive prochiral ketones was explored.